Peer Victimization and Dating Violence Victimization: The Mediating Role of Loneliness, Depressed Mood, and Life Satisfaction - Cava, María-Jesús (Journal of interpersonal violence, 2021)
Peer victimization and dating violence victimization have serious negative effects on adolescents’ health, and they seem to be related. However, the mediating processes in this relationship have not been sufficiently analyzed. The purpose of this study was to analyze the direct and indirect relationships between peer victimization and dating violence victimization, considering the possible mediator role of loneliness, depressed mood, and life satisfaction. These relationships are analyzed in boys and girls, and in early and middle adolescence. From an initial sample of 1,038 Spanish adolescents, those who had or had had in the past 12 months a dating relationship (647 adolescents; 49.1% boys, M = 14.38, SD = 1.43) were included in this study. Multigroup structural equation modeling was used to test a double mediation model simultaneously for boys and girls, testing the invariance of the relationships among variables across genders. The same technique was used to test the model simultaneously for early and middle adolescence, testing the invariance of the relationships among variables across age groups. Results revealed a positive direct relationship between peer victimization and dating violence victimization, as well as the partial mediating role of loneliness and life satisfaction in this relationship. The mediator role of depressed mood was not supported. The same mediational model was confirmed in boys and girls, and in early and middle adolescence. These results highlight the important role of loneliness and life satisfaction to explain the link between peer victimization and dating violence victimization in adolescence. These findings may be useful for developing intervention programs aimed at preventing situations of multiple victimization during adolescence.